Comparison of the Efficacy of Polyvinyl Alcohol Colorless Embolic Microspheres (8Spheres) and Gelatin Embolic Microspheres (Embosphere) in Uterine Artery Embolization for Symptomatic Uterine Fibroids in Women Without Fertility Requirements: A Multicenter Observational Study - Gao S; Li F; Song F; Zhang X; Wang Y; Wang J (International Journal of Women's Health, 2025)
Songkun Gao,1,* Fengshuang Li,1,* Fang Song,1 Xiaofeng Zhang,2 Yan Wang,1 Jiandong Wang1 1Department of Gynecologic Oncology, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Beijing, 100026, People’s Republic of China; 2Department of Radiology,Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Beijing, 100026, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan Wang, Department of Gynecologic Oncology, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Qihelou Street, Dongcheng District, Beijing, 100006, People’s Republic of China, Email wwyy3196@ccmu.edu.cn Jiandong Wang, Department of Gynecologic Oncology, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing Maternal and Child Health Care Hospital, Qihelou Street, Dongcheng District, Beijing, 100006, People’s Republic of China, Email wangjiandongxy@ccmu.edu.cnObjective: To evaluate the differences in efficacy between polyvinyl alcohol colorless embolic microspheres (8Spheres®) and gelatin embolic microspheres (Embosphere®) in uterine artery embolization for symptomatic uterine fibroids.Methods: We included 259 patients from 12 hospitals who underwent uterine artery embolization for symptomatic uterine fibroids. We collected preoperative general conditions, menstrual status, and uterine and fibroid sizes as indicated by magnetic resonance imaging, as well as changes in ovarian hormone levels before and 6 months after the procedure. Differences in uterine fibroid scores and health-related quality of life scores between the two types of microspheres were compared using analysis of covariance (ANCOVA). Differences in the largest fibroid volume, uterine volume, total menstrual bleeding score, and ovarian hormone levels were compared using T-tests or Mann–Whitney U-tests.Results: There was no significant difference in clinical efficacy between the two types of microspheres at 6 months postoperatively (P=0.4081). No significant differences were observed in uterine fibroid volume or symptom-related scores.There were no significant differences in ovarian hormone levels between the two groups or within each group before and after the procedure.Conclusion: The use of 8Spheres® is effective for symptomatic uterine fibroids and is comparable to the currently clinically used Embosphere® microspheres in terms of efficacy for symptomatic uterine fibroids.Keywords: symptomatic uterine fibroids, uterine artery embolization, polyvinyl alcohol colorless embolic microspheres, gelatin embolic microspheres